Effect of hot air, solar and sun drying treatments on protavitamin A retention in orange-fleshed sweetpotato - Bechoff, Aurélie; Dufour, D.L.; Dhuique-Mayer, Claudie; Marouzé, Claude; Reynes, M; Westby, Andrew (2009)
Different drying treatments, cross flow, greenhouse solar, and open-air sun, were applied to an American orange-fleshed sweetpotato variety. Trans-?-carotene losses in flour made from dried chips varied between 16 and 34% in all treatments. Hot air cross flow drying retained significantly more provitamin A than sun drying. Solar and sun drying were not significantly different in terms of provitamin A retention. The shape of the sweetpotato pieces (chip or crimped slice) influenced provitamin A retention during sun-drying; crimped slices retained more provitamin A. Other minor provitamin A compounds in fresh sweetpotato included 13-cis and 9-cis-?-carotene and ?-carotene 5,6-epoxide. No significant increase in the cis-isomers was observed after drying.